Does greater workload lead to reduced quality of preventive and curative care among community health workers in Bangladesh? - Puett, Chloe; Coates, Jennifer; Alderman, Harold; Sadruddin, Salim; Sadler, Kate (SAGE Publications, 2012)
Community health workers (CHWs) perform a range of important tasks; however, limited evidence is available regarding the association between their workload and the quality of care they provide.To analyze the quality of preventive and curative care provided by two groups of CHWs with different workloads in southern Bangladesh.One group of CHWs provided preventive care in addition to implementing community case management (CCM) of acute respiratory infection and diarrhea, and another group additionally treated severe acute malnutrition (SAM). Preventive care was measured by case management observation at a routine household visit. Curative care was measured by case scenarios. Qualitative methods were used to contextualize CHWs' performance by examining their perceptions of challenges related to their workload. A total of 338 CHWs were assessed.CHWs managing cases of SAM worked significantly more hours than the other group (16.7 ± 6.9 hours compared with 13.3 ± 4.6 hours weekly, p < .001) but maintained quality of care on curative and preventive work tasks. Effectively treating cases of SAM appeared to motivate CHWs.This was one of the first trials adding the treatment of SAM to a CHW workload and suggests that adding SAM to a well-trained and supervised CHW's workload, including preventive and curative tasks, does not necessarily yield lower quality of care. However, increased workloads had consequences for CHWs' domestic life, and further increases in workload may not be possible without additional incentives.